Bibliometric Analysis of Trends and Developments in Agile Project Management - Loso Judijanto; Arief Yanto Rukmana; Mislan Sihite; Arnes Yuli Vandika (Westscience Press, 2024)
This study employs a comprehensive bibliometric analysis to explore the evolution, trends, and research networks within the field of Agile Project Management (APM). Utilizing data from prominent academic databases and visualized through VOSviewer, this paper identifies thematic clusters that highlight foundational Agile principles, strategic implementations, team dynamics, and technical aspects of APM. The research trends over the past decade demonstrate a significant shift from basic Agile methodologies towards advanced topics like risk and cost management, reflecting the field's maturation and adaptation to diverse and complex environments. The analysis also uncovers substantial research opportunities in integrating Agile practices with cost management, applying Agile in non-traditional fields, and developing sophisticated risk management strategies. Moreover, an examination of author collaboration networks reveals distinct clusters of scholarly activity and highlights influential researchers and their interrelationships. This study provides valuable insights into the dynamic landscape of Agile Project Management research, underscoring both established areas and emerging frontiers for future exploration.